2016
DOI: 10.22495/rcgv6i4c3art2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of banking services: Factors for bank’s preference

Abstract: The paper examined consumer perceptions of banking services as a factor for bank’s preference among open and distance learning students. Survey research method was adopted. The population of study was the ODL students from which sample were selected using stratified random sampling technique. Questionnaire was administered on selected samples. The research instrument was validated through content validity while reliability was done through test-re-test method. Respondents’ perceptions of banking services were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results of studies on the determinants of bank customers' preferences show some variation, depending on the specificity of the methodology, the adopted research perspective and the objectives (Srinivas, 2021;Adefulu, 2016;Dehnert, 2022;Dehnert, 2022).…”
Section: Specificationmentioning
confidence: 99%
“…The results of studies on the determinants of bank customers' preferences show some variation, depending on the specificity of the methodology, the adopted research perspective and the objectives (Srinivas, 2021;Adefulu, 2016;Dehnert, 2022;Dehnert, 2022).…”
Section: Specificationmentioning
confidence: 99%
“…Ease of use, Efficiency, Availability, Confidentiality, and awareness is essential for the selection of banking services. Adesoga & Louise (2016) examined customer perception of banking services as factors for a bank's performance. A survey research method was used and component factor analysis and T-tests were used to analyze data.…”
Section: Customer Perception On Financial Inclusionmentioning
confidence: 99%
“…A survey research method was used and component factor analysis and T-tests were used to analyze data. The study concluded that the most potent factors are customers treated competently with professionalism by the employees, strong commitment to meeting customers' needs, and interaction with the user (Adesoga & Louise, 2016). Therefore, banks' services must be customeroriented and customer relationship-focused.…”
Section: Customer Perception On Financial Inclusionmentioning
confidence: 99%